Strategi Guru Akidah Akhlak dalam Pendidikan Karakter pada Siswa Kelas VIII MTs Darul Falah Rembul Kecamatan Randudongkal Kabupaten Pemalang - Bahtiar, Ain (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Character education for students is something that is very important to do continuously. This is done because of increasingly sophisticated developments and the influence of technology which is increasingly rampant, especially for teenagers who still have labyrinthine minds who need guidance from parents, teachers and people around them. The formulation of the problem in this research is what is the character of class VIII students at MTs Darul Falah Rembul, Randudongkal District, Pemalang Regency, what are the strategies of the moral aqidah teacher in character education for class VIII students at MTs Darul Falah Rembul, Randudongkal District, Pemalang Regency, what are the supporting and inhibiting factors for the strategy of the teacher of moral aqidah in character education for class VIII students at MTs Darul Falah Rembul Randudongkal District, Pemalang Regency. The purpose of this research is to determine the character of class VIII students at MTs Darul Falah Rembul, Randudongkal District, Pemalang Regency, to find out the moral aqidah teacher's strategy in character education for class VIII students at MTs Darul Falah Rembul, Randudongkal District, Pemalang Regency, to determine the supporting and inhibiting factors for teacher strategies. Moral beliefs in character education for class VIII students at MTs Darul Falah Rembul, Randudongkal District, Pemalang Regency. This type of research is a field study. Meanwhile, the approach used is a qualitative approach. Meanwhile, the data collection methods in this research are observation, interviews and documentation. Meanwhile, in analyzing the data, researchers used descriptive analysis. The results of this research show that: first: the character of MTs Darul Falah Rembul students is categorized as quite good. These characters or attitudes include enjoying congregational prayers, mid-day prayers, reciting the Qur'an, being polite to teachers and seniors and liking to help each other, being honest and happy to share with friends and being merciful to others both during online learning and before learning from home. Second: the teacher's strategy of moral aqidah in student character education includes: Mujahadah/training, habituation and giving incentives, teacher example and character education which is included in the learning process. Third: supporting factors for character education include: family factors, community environment and madrasah environment, while inhibiting factors for character education include internal factors: children's characteristics from childhood due to lack of parental supervision and external factors: the influence of the era of globalization in the form of electronic media and social media which can have a negative impact on students in influencing student character education.